Gerakan Edukasi Mengenal Mental Disorder Lebih Dekat “HONEY: Helping Others Notice & Educate Yourself about Schizophrenia” - Veronica, Fifi; Fitri, Lulu Lusianti; Nurhulwah, Tahlirsti D.; Amaris, Oshara R.; Kangdra, Evelyn; Angelia, Laura Y.; Aura, Tuhfatu B.; Nababan, Dwi V.; Zahra, Aurellia G.; Syuaib, Noura A.; Rizlani, Aliyah F. (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Early detection in schizophrenia are important in treatment of mental disorder in psychiatric care. Therefore, it is necessary to increase knowledge of schizophrenia among the general public. Integrated Curriculum in Medical Faculty Universitas Padjadjaran provide the promotive and preventive health system into their activities and video education as part of their implementation curriculum. Before the activities, 180 responden fill the pre assesment survey and only 88 responden allowed the next step to viewing the video and fill the quesionnaire pre dan post test based on Knowledge About Schizophrenia Test (KAST), The result show increasing of knowledge 13.11%. Our video education program “ HONEY” was useful in helping acquire a basic knowledge of schizophrenia and discriminate correctly the symptoms of schizophrenia